The Influence of Indisulam on Human Immune Effector Cells: Is a Combination with Immunotherapy Feasible? - Arnet, Lisa; Emilius, Lisabeth; Hamann, Annett; Carmo-Fonseca, Maria; Berking, Carola; Dörrie, Jan; Schaft, Niels (Pharmaceutics, 2025)
Background: As a modulator of pre-mRNA splicing, the anti-cancer agent indisulam can induce aberrantly spliced neoantigens, enabling immunologic anti-tumor activity. Consequently, combining indisulam with immunotherapy is expected to be a promising novel approach in cancer therapy. However, a prerequisite for such a combination is that immune effector cells remain functional and unharmed by the chemical. Methods: To ensure the immunocompetence of human immune effector cells is maintained, we investigated the influence of indisulam on ex vivo-isolated T cells and monocyte-derived dendritic cells (moDCs) from healthy donors. We used indisulam concentrations from 0.625 µM to 160 µM and examined the impact on the following: (i) the activation of CD4+ and CD8+ T cells by CD3-crosslinking and via a high-affinity TCR, (ii) the cytotoxicity of CD8+ T cells, (iii) the maturation process of moDCs, and (iv) antigen-specific CD8+ T cell priming. Results: We observed dose-dependent inhibitory effects of indisulam, and substantial inhibition occurred at concentrations around 10 µM, but the various functions of the immune system exhibited different sensitivities. The weaker activation of T cells via CD3-crosslinking was more sensitive than the stronger activation via the high-affinity TCR. T cells remained capable of killing tumor cells after treatment with indisulam up to 40 µM, but T cell cytotoxicity was impaired at 160 µM indisulam. While moDC maturation was also rather resistant, T cell priming was almost completely abolished at a concentration of 10 µM. Conclusions: These effects should be considered in possible future combinations of immunotherapy with the mRNA splicing inhibitor indisulam.
CRIS-Team Scopus Importer:2025-04-04
Keywords: dendritic cells; immunotherapy; indisulam (E7070); neoantigens; T cells